2006
DOI: 10.1002/cncr.21945
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptors‐α and ‐β in bladder cancer cell lines and human bladder tumor tissue

Abstract: We report a case of a newborn infant who had simultaneous sialoblastoma and hepatoblastoma tumours at birth. The diagnoses were made on post mortem examination. Both of these are rare tumours in the neonatal period. Pediatr Blood Cancer 2009;52:883–885. © 2009 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
3
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(170 citation statements)
references
References 23 publications
8
157
3
2
Order By: Relevance
“…Our finding that immortalized and tumor urothelial cells also express significantly higher levels of PCNA than primary cells supports the concept that immortalization, malignant transformation, recurrence, and the development of muscle invasion of human bladder tumor are accompanied by increased expression of PCNA (Syrigos et al 2004). One study reported that bladder cancers express high levels of ERb but low levels of ERa; however, this report considered tumors with 10% or fewer cells expressing ERa as negative for ERa (Shen et al 2006). Thus, low expression of ERa was equaled with no expression.…”
Section: Discussionsupporting
confidence: 81%
“…Our finding that immortalized and tumor urothelial cells also express significantly higher levels of PCNA than primary cells supports the concept that immortalization, malignant transformation, recurrence, and the development of muscle invasion of human bladder tumor are accompanied by increased expression of PCNA (Syrigos et al 2004). One study reported that bladder cancers express high levels of ERb but low levels of ERa; however, this report considered tumors with 10% or fewer cells expressing ERa as negative for ERa (Shen et al 2006). Thus, low expression of ERa was equaled with no expression.…”
Section: Discussionsupporting
confidence: 81%
“…They share several functionally conserved structural domains such as the regions responsible for DNA binding, dimerization, ligand binding and ligand-dependent transactivation of gene expression. 72 ERa and ERb have different transcriptional activities in certain ligand, cell type and promoter contexts and also exhibit distinct tissue-and cell type-specific expression patterns. ERa is found predominantly in the normal pituitary, breast, uterus, vagina, testis, liver and kidney, whereas ERb is mainly expressed in thyroid, ovary, prostate, skin, bladder, lungs, gastrointestinal tract, bone and cartilage.…”
mentioning
confidence: 99%
“…In addition, FHL1 interacts with estrogen receptors and inhibits breast cancer cell growth (24,25). Moreover, estrogen receptors are highly expressed in BC and contribute to BC cell proliferation (26,27). Thus, previous and current findings lead us to think that FHL1 might have a tumor suppressive function through interaction with p21, c-myc, and estrogen receptors in BC.…”
Section: Discussionmentioning
confidence: 86%